Proverbs: wisdom calls : an introduction and study guide - Schwáb, Zoltán S. (T&T Clark's study guides to the Old Testament, 2023)
"Introduces the Book of Proverbs, examining its characteristics, historical context and key themes, and encouraging existential engagement with Proverbs"--